Financial distress and corporate acquisitions: further empirical evidence - Kahya, Emel; Saidi, Reza; Theodossiou, Panayiotis (My University, 1996)
The previous results suggest that financial leverage, profitability, managerial effectiveness, the firm's growth and size are important explanatory variables in financial distress models. These findings are consistent with theoretical bankruptcy models demonstrating leverage to be positively related to the probability of bankruptcy while operating income (EBIT - Interest expense) is shown to be negatively related to the probability of bankruptcy, e.g., Scott (1977). The firm's growth and managerial effectiveness are directly related to the firm's future cash flow stream. Therefore, they are negatively related to the probability of distress. The justification for the size variable can be found in the 'imperfect access to external capital' model conjecture. That is, larger firms are expected to have better access to capital markets, therefore the flotation costs associated with raising additional funds for new projects or meeting debt obligations are proportionally lower (Scott, 1981, pp. 332-338). Under these circumstances larger firms tend to have a lower probability of failure. Interestingly, none of the liquidity ratios is a significant explanatory variable, despite the fact that these measures were found to be important determinants in past empirical papers. Moreover, the results indicate that the sales generating ability of the firm, inefficient management, proportion of productive assets to total assets and return on productive assets are positively related to the probability of acquisition of a financially-distressed firm. Insider control and financial leverage, on the other hand, are negatively related to the probability of acquisition. The ratio of sales to total assets has the highest impact on the probability of acquisition which indicates that acquiring firms place heavy emphasis on the sales generating ability of a distressed firm's assets. The ratio of inventory to sales measures management's effectiveness in turning inventories into sales and is used as a proxy for managerial inefficiency (higher values of this ratio are indicative of inefficient management). This ratio is positively related to the probability of acquisition, therefore providing support to the 'inefficient management rationale' for a merger. Efficiently managed firms will acquire an inefficient firm and through competent management increase its efficiency and market value. The percentage of a firm's fixed assets (productive assets) to total assets and the return on these assets positively influence the decision of the acquiring firm to acquire a distressed firm. Clearly, a firm with profitable fixed assets is easier to restructure and make profitable. Insider control is found to have a negative impact on the probability of acquisition of a financially distressed firm. As previously discussed, this can be attributed to the fact that insiders (e.g., directors and top managers) of distressed firms are usually replaced after the takeover, whereas insiders of firms in bankruptcy proceedings hold their positions for a longer period of time (e.g., Ang and Chua, 1981; and Jensen and Ruback, 1983). Financial leverage has a negative sign indicating that, other things being equal, the more leveraged the firm, the lower the probability of acquisition. One reason for this phenomenon is that the acquisition of a highly leveraged firm increases the debt ratio of the acquiring firm beyond its optimal level resulting in a reduction of its market value. Also, higher leverage increases the likelihood of default for the acquiring firm. The negative relationship between leverage and probability of acquisition can also provide additional support to management's practice of increasing the firm's leverage as a deterrent to a takeover (Stulz, 1988)
Keywords: Finance; Accounting; Business; Mathematical models